2017
DOI: 10.1093/infdis/jix585
|View full text |Cite
|
Sign up to set email alerts
|

Ascaris Suum Infection Downregulates Inflammatory Pathways in the Pig Intestine In Vivo and in Human Dendritic Cells In Vitro

Abstract: Ascaris suum is a helminth parasite of pigs closely related to its human counterpart, A. lumbricoides, which infects almost 1 billion people. Ascaris is thought to modulate host immune and inflammatory responses, which may drive immune hyporesponsiveness during chronic infections. Using transcriptomic analysis, we show here that pigs with a chronic A. suum infection have a substantial suppression of inflammatory pathways in the intestinal mucosa, with a broad downregulation of genes encoding cytokines and anti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
37
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 34 publications
(41 citation statements)
references
References 40 publications
4
37
0
Order By: Relevance
“…58,59 Our analysis of the early transcriptional profile of helminth PCF-treated LPS + IFN-c-matured moDCs supports these previous findings and suggests that helminth PCF may interfere with TLR4 signaling to exert its immunosuppressive effects, as indicated by identification of decreased expression of molecules downstream of TLR4 activation. 58,59 Our analysis of the early transcriptional profile of helminth PCF-treated LPS + IFN-c-matured moDCs supports these previous findings and suggests that helminth PCF may interfere with TLR4 signaling to exert its immunosuppressive effects, as indicated by identification of decreased expression of molecules downstream of TLR4 activation.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…58,59 Our analysis of the early transcriptional profile of helminth PCF-treated LPS + IFN-c-matured moDCs supports these previous findings and suggests that helminth PCF may interfere with TLR4 signaling to exert its immunosuppressive effects, as indicated by identification of decreased expression of molecules downstream of TLR4 activation. 58,59 Our analysis of the early transcriptional profile of helminth PCF-treated LPS + IFN-c-matured moDCs supports these previous findings and suggests that helminth PCF may interfere with TLR4 signaling to exert its immunosuppressive effects, as indicated by identification of decreased expression of molecules downstream of TLR4 activation.…”
Section: Discussionsupporting
confidence: 86%
“…14,17,18,20 In soluble egg antigen, one of the multiple compounds that can induce DC-mediated Th2 immune responses is omega-1; a glycosylated T2 RNase that can inhibit pro-inflammatory protein synthesis, induce strong surface expression of OX40L on DCs and increase the IL-4/IFN-c ratio in DCs and allogenic naive CD4 + T-cell co-culturing experiments. 20 The observations in our study, and the study by Midttun et al 58 that helminth PCF down-regulated PTGS2 transcripts as well as COX-2 protein levels indicate that helminth PCF-treated moDCs might not be able to induce prostaglandin E 2 -dependent DC-mediated Th2 responses. 58 Moreover, a recent study showed that soluble egg antigen treatment of DCs induced prostaglandin E 2 synthesis, resulting in autocrine induced OX40L, which further primed DCs to initiate Th2 responses.…”
Section: Discussionsupporting
confidence: 54%
See 1 more Smart Citation
“…Similarly, helminth parasites are known to have strong immunomodulatory properties, affecting responses to third party antigens, including dampening host responses to cholera and mycoplasma vaccinations . These modulatory effects may be closely linked to DC function as products from the porcine whipworm Trichuris suis supress production of TLR‐4‐associated cytokines in human DCs in vitro, whilst body fluid derived from the roundworms Ascaris lumbricoides or A. suum can interfere with LPS‐induced maturation and/or function of human and murine DCs …”
Section: Introductionmentioning
confidence: 99%
“…This has also been investigated in pigs using transcriptomic analysis, showing that chronic A. suum infection induces suppression of inflammatory pathways in the intestinal mucosa, downregulating genes encoding cytokines and antigen-processing and co-stimulatory molecules. This effect was reproduced by A. suum body fluid in human dendritic cells (DCs) in vitro [26]. However, few of the immunomodulatory molecules found in excretory/ secretory products of these species have been characterized, among them PAS-1 has been extensively studied [27].…”
Section: Helminth-driven Immunomodulationmentioning
confidence: 99%